2009
DOI: 10.1007/s00421-009-1214-3
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of passive stretching on the electromechanical delay and evoked twitch properties

Abstract: The purpose of this study was to investigate the acute effects of passive stretching on the electromechanical delay (EMD), peak twitch force (PTF), rate of force development (RFD), and compound muscle action potential (M-wave) amplitude during evoked twitches of the plantar flexor muscles. 16 men (mean age +/- SD = 21.1 +/- 1.7 years; body mass = 75.9 +/- 11.4 kg; height = 176.5 +/- 8.6 cm) participated in this study. A single, square-wave, supramaximal transcutaneous electrical stimulus was delivered to the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
62
0
15

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(86 citation statements)
references
References 60 publications
(186 reference statements)
9
62
0
15
Order By: Relevance
“…Although, flexibility or stretching routines are currently recommended as part of an exercise session, surprisingly the prescription tend to be general and non-individualized. On the other hand, more often these exercises are included at the end of the session, attempting to avoid potential deleterious effects on strength performance (Costa et al 2011(Costa et al , 2010Gleim and McHugh 1997;Rubini et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Although, flexibility or stretching routines are currently recommended as part of an exercise session, surprisingly the prescription tend to be general and non-individualized. On the other hand, more often these exercises are included at the end of the session, attempting to avoid potential deleterious effects on strength performance (Costa et al 2011(Costa et al , 2010Gleim and McHugh 1997;Rubini et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…5 In addition, the duration of EMD is dependent on the mechanical properties of tendon structures. 24 It is speculated that a decrease in stiffness of tendon structures, which means a decrease in the ability to transmit muscle force, plays an important role in increasing the duration of the EMD.…”
Section: Discussion Tmentioning
confidence: 99%
“…EMD is affected by muscle fatigue, 29 muscle length, 21 muscle training, 11,17,19 passive muscle stretching, 5 and the type of muscle activation. 15 Indeed, it has been reported that VL and peroneus longus EMDs were significantly longer in patients with anterior cruciate ligament reconstruction 15 and unstable ankles, 13,20 respectively, compared to healthy individuals.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Além do reflexo do estiramento muscular dependente da velocidade em que há o aumento da resistência à movimentação passiva, a espasticidade tem como consequências a restrição da amplitude articular, o que interfere na função motora dificultando atividades, causando dor, desconforto muscular, deformidades ou mesmo contraturas (CHEN, et al, 2005;COSTA et al, 2010;LEE et al, 2008;RODGERS et al, 2010;TIEVE;ZONTA;KUMAGAI, 1998).…”
Section: Espasticidade E Alteração De Forçaunclassified